Three Port Laparoscopic Cholecystectomy by a Modified Technique (Journal of Shaheed Suhrawardy Medical College, 2022)
Introduction:Since the introduction of laparoscopic cholecystectomy (LC) several modifications have been introduced to its procedure. Main aim of these modifications is to improve cosmesis & reduce pain. Several institutes are routinely performing conventional 3 ports laparoscopic. In modified 3 ports LC, the third port was moved from right hypochondrium to umbilicus, to conceal it in the umbilical scar, thereby giving the three port comfort to the surgeon and two port benefits to the patient.Methods: This observational study was conducted in the Department of Surgery of Shaheed Suhrawardy Medical College & Hospital from September 2015 to October 2016. After taking valid consent a total 45 patients were selected for modified 3 ports LC. Here we tried to see the safety and benefit of this modified technique by assessing operating time, intra-operative complications, open conversion rate, postoperative wound infection, post-operative hospital stay, pain score and satisfaction with cosmetic outcome.Results: 3 patients were excluded from study due to different reasons. So, among total 42 (N) patients 30 (71.4%) were female & 12 (28.6%) were male. Operative time was 58.48 ± 32.52 minutes (range 34 to 180 minutes). 2 patients required conversion to open surgery. Pain score was 2.07 ±1.71 and cosmetic score was 8.67 ± 1.99.Conclusion: Modified 3 port laparoscopic cholecystectomy can be performed safely with a higher cosmetic satisfaction in selected cases by expert surgeon.J Shaheed Suhrawardy Med Coll 2020; 12(2): 90-94